1993
DOI: 10.1002/jbmr.5650081013
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species activate and tetracyclines inhibit rat osteoblast collagenase

Abstract: Recent studies have demonstrated that tetracyclines (TCs) scavenge reactive oxygen species (ROS). Hypochlorous acid (HOCl), an ROS produced by neutrophils, has been shown to activate neutrophil procollagenase. The objective of the present study was to determine whether (1) HOCl also activated osteoblast procollagenase and (2) TCs inhibited this enzyme in the presence of HOCl. HOCl (5 microM) activated the proenzyme approximately sixfold (P < 0.01) from the medium of PTH-treated UMR-106-01 osteoblastic osteosar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 42 publications
2
30
0
2
Order By: Relevance
“…release mechanisms in diabetic cardiomyocytes. Previous studies, which are supporting our present data, have also shown that doxycycline has some ability to inhibit ROS [32,33]. Ramamurthy et al [33] showed that 50-100 lM tetracyclines were necessary to prevent hypochlorite activation of pro-collagenase, although less than 30 lM is required to inhibit MMP activity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…release mechanisms in diabetic cardiomyocytes. Previous studies, which are supporting our present data, have also shown that doxycycline has some ability to inhibit ROS [32,33]. Ramamurthy et al [33] showed that 50-100 lM tetracyclines were necessary to prevent hypochlorite activation of pro-collagenase, although less than 30 lM is required to inhibit MMP activity.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies, which are supporting our present data, have also shown that doxycycline has some ability to inhibit ROS [32,33]. Ramamurthy et al [33] showed that 50-100 lM tetracyclines were necessary to prevent hypochlorite activation of pro-collagenase, although less than 30 lM is required to inhibit MMP activity. Akamatsu et al [32] showed that 2 lM doxycycline would inhibit in vitro systems generating superoxide, hydroxyl, or hydrogen peroxide by 0, 16, and 22%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have also shown that doxycycline has some ability to inhibit reactive oxygen species (ROS) [24]. Although we cannot exclude the possibility that doxycycline may have other protective effects because of its reported pleiotropic actions including inhibition of proinflammatory cytokines and ROS, it is plausible that, to the plasma concentration achievable with the dose of doxycycline used in our study [13], MMP inhibition, as opposed to ROS scavenging, may be the main mechanism of its protective action [25].…”
Section: Discussionmentioning
confidence: 81%
“…30 The inhibition of the enzymatic activity of MMPs could be attributable to doxycycline binding to the zinc/calcium at their catalytic sites. 29 In addition, doxycycline could inhibit the activation of pro-MMPs by suppressing oxidative stress 26,38 and by promoting proteolysis of pro-MMPs into enzymatically inactive fragments. 29 The reduction in MMP protein expression could also result from the decreased steady-state levels of MMP mRNA.…”
Section: Chung Et Al Doxycycline Ameliorates Taa In Marfan Syndrome E79mentioning
confidence: 99%